Fingermark visualisation on uncirculated £5 (Bank of England) polymer notes: Initial process comparison studies. (June 2017) - Downham, Rory P.; Brewer, Eleigh R.; King, Roberto S.P.; Luscombe, Aoife M.; Sears, Vaughn G.
Highlights: Fingermark processes were tested with natural marks donated on to banknotes. 14 processes were compared, including the recent fp Natural 2 (Nat2) powder product. Initial assessments were made under typical process (primary) viewing conditions. The addition of infrared reflection and lifting techniques improved capability. Nat2, multimetal deposition and powder suspensions showed the greatest potential. Abstract: Experiments were conducted to investigate the effectiveness of a range of fingermark visualisation processes on brand new, uncirculated, £5 polymer banknotes (and their test note predecessors), as produced by the Bank of England (BoE). In the main study of this paper, a total of 14 individual processes were investigated on BoE £5 polymer banknotes, which included both 'Category A' processes (as recommended in the Home Office Fingermark Visualisation Manual) as well as recently developed processes, including fp Natural ® 2 powder (cuprorivaite) from Foster + Freeman and a vacuum metal deposition sequence that evaporates silver followed by zinc. Results from this preliminary investigation indicate that fp Natural ® 2, multimetal deposition, Wet Powder ™ Black, iron oxide powder suspension and black magnetic powder are the most effective processes on these uncirculated £5 BoE polymer banknotes, when viewed under "primary viewing" conditions (white light or fluorescence). Additional fingermarks were visualised on the polymer banknotes following the subsequent use of reflected infrared imaging and lifting techniques, and with the benefit of these techniques taken into consideration, the aforementioned processes remained amongst the most effective overall. This work provides initial insight into fingermark visualisation strategies for BoE £5 polymer banknotes, and the need for further studies in order to generate mature operational guidance is emphasised.